Income Tax Policy on Fringe Benefits in Indonesia: A Systematic Literature Review - Dwi Septya Pratiwi; Prianto Budi Saptono (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
The income tax treatment of fringe benefits following the Harmonization of Tax Regulations (HPP) Law has changed to a taxable–deductible method. This change was triggered by unfair tax treatment, potential tax loss, and aggressive tax planning. The imposition of tax on fringe benefits aims to address these issues. This study aims to analyze the regulation, impact, and challenges of income tax policy on fringe benefits in Indonesia. A systematic literature review (SLR) was conducted using articles published between 2021 and 2025, sourced from Google Scholar and ScienceDirect. From an initial 605 articles, 23 met the selection criteria, and 7 were selected for final analysis. The analysis revealed positive impacts from the implementation of income tax on fringe benefits, namely creating tax fairness, increasing tax revenue, and closing gaps for aggressive tax avoidance. Changes in taxpayer behavior can also be observed as a result of this policy. However, this policy also presents challenges, particularly in determining the valuation of fringe benefits as the basis for tax imposition. Therefore, clearer guidelines and in-depth socialization are needed to facilitate taxpayers in determining the tax base and to enhance compliance.